FROM HIGH ASPIRATIONS TO HARSH REALITY: EU HUMAN RIGHTS PROMOTION AT THE UN HUMAN RIGHTS COUNCIL - A. S. Boyashov (Vestnik MGIMO-Universiteta)
Since 1990s the EU has been highly aspirational on its role in human rights promotion on a global scale, which has led to the EU’s proactive participation in international organizations. The Union identifies itself as ‘global human rights force’ but less and less acts in accordance with that identity at the UN HRC. At this intergovernmental body the EU acts as a smoothly coordinated block, which is contested by the other regional and political coalitions of states. The emerged multi-polar world system urges for a less normative analysis of EU human rights promotion. The article proposes and applies 4 measurable indicators to assess the EU actorness in human rights promotion: 1) explicitness of references to the UN or global fora in the EU primary law and secondary legislation related to human rights promotion; 2) degree of support/contestation for the EU objectives by other non-EU actors at the HRC; 3) degree of (in)cohesiveness of EU external representation at the HRC; 4) EU (in)consistency in formulating priorities and using instruments at the HRC. Multi-polar world system questions the EU high aspirations as ‘a global force’ in human rights promotion. The EU ability to use its instruments in human rights promotion is moderate even despite its enhanced burden sharing among the EU member states, a hybrid system of representation, a vast diplomatic and NGOs’ network. ‘Big’ states still play the leading role in this process. The internal disagreement among the EU member states weakens the EU human rights promotion. The UN HRC structural context limits the EU opportunity to promote human rights, therefore, the EU tries to be less loud and less visible.